Ground cover management affects parasitism of Prays oleae (Bernard) - Villa, María (2016)
Spontaneous ground covers comprise ecological infrastructures that may provide food, alternative hosts and shelter for parasitoids in olive groves, thus contributing to biological control of pests. This study investigated the effects of herbicide application, tillage, and conservation of spontaneous ground covers on parasitism of the anthophagous generation of the olive moth, Prays oleae (Bernard). The study was performed in northeast Portugal in 2011 and 2013 in 14 and 15 olive groves, respectively, with different management types. Generalized Estimating Equations (GEE) were used to analyze olive moth emergence, overall parasitism rate, relative abundance of parasitoid species, and total parasitismof olive moth larvae. Ageniaspis fuscicollis (Dalman) accounted for the majority of the parasitism, followed by Elasmus flabellatus (Fonscolombe). In both years, ground cover management type did not influence the emergence rate of P. oleae. However, overall parasitism rate, emergence of A. fuscicollis, and the number of A. fuscicollis emerging per olive moth larvae varied among years. In 2011, the latter response variables were significantly higher in groves with spontaneous ground cover than in those treated with herbicide, indicating a negative effect of herbicides on parasitoids. Although tilled groves obtained higher values for these variables in 2013, parasitism rates were generally very low. In sum, the management of ground covers seemed to influence the overall rate of P. oleae parasitism in some years, but longer-term experiments are needed to clarify this trend.